Method for improving cycle performance of manganese-based positive electrode material, prepared manganese-based positive electrode material and application
By applying a magnetic field and/or high-temperature plasma treatment during calcination, the spin state of manganese ions in the manganese-based positive electrode material is solved, and the electrochemical performance of manganese-based positive electrode material is reduced during the cycle, achieving higher cycles Stability and electrochemical properties.
Patent Information
- Application Number
- CN202411665126.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
During the circulation process, manganese-based positive electrode materials have problems such as irreversible oxygen release, transition metal ion migration, dissolution and surface side reactions, resulting in a decline in electrochemical performance and hindering its commercialization process.
By applying a magnetic field and/or high-temperature plasma treatment during calcination, the spin state of manganese ions in the manganese-based positive electrode material is reduced, thereby preparing a manganese-based positive electrode material with a low spin state.
It significantly improves the cycle stability and electrochemical performance of manganese-based positive electrode materials, extends the service life of the battery, and at the same time, the process is simple and pollution-free, suitable for large-scale applications.
Smart Images

Figure CN119461507A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery preparation, and particularly relates to a method for improving the cycling performance of a manganese-based cathode material, the obtained manganese-based cathode material and its application. Background Art
[0002] Due to the characteristics of relatively rich manganese resources, relatively low cost, and relatively high voltage of manganese-based materials, manganese-based cathode materials have received extensive attention. Manganese-based cathode materials include, for example, lithium manganate, spinel nickel manganese lithium oxide, layered sodium manganese material, lithium iron manganese phosphate, and lithium-rich manganese-based materials. Among them, the lithium-rich manganese-based layered material is based on the traditional layered material, with the lithium content increased, and lithium replacing the transition metal ions in the transition metal layer to obtain a lithium-rich manganese-based layered cathode material, whose chemical formula is xLi2MnO3·(1-x)LiTMO2(0<x<1, TM = Mn, Ni, Co, etc.), and can also be written as Li 1+x TM 1-x O2. Among many lithium-ion battery cathode materials, due to the high specific capacity (250 mAh·g -1 ), high working voltage (>3.5 V), low cost, and environmental friendliness of the lithium-rich manganese-based layered cathode material, it is considered to be the key cathode material for building lithium-ion batteries to break through 500 Wh·kg -1 . However, the following problems also exist, which hinder its commercialization process:
[0003] (1) Irreversible oxygen release
[0004] When charging to 4.8 V in the first cycle, it is difficult to control the oxidation-reduction process of anions. Some O 2- undergoes a peroxidation reaction and is oxidized to O2. Some of the O2 is trapped in the bulk phase, and the other part is irreversibly released through the surface. The anion oxidation-reduction reaction is a double-edged sword. On the one hand, compared with ternary materials, it provides more capacity for the material. On the other hand, O2 can only be partially reduced to O 2- during the subsequent discharge process, resulting in a lower initial Coulomb efficiency and voltage hysteresis. At the same time, long-term cycling will also promote the loss of O2 from the bulk phase and the formation of microstructural defects, accelerating voltage decay.
[0005] (2) Transition metal ion migration
[0006] When charging to 4.8 V, lithium ions in the transition metal layer are removed, and at the same time, anions undergo an oxidation reaction as charge compensation. At this time, transition metal ions will undergo interlayer migration and intralayer migration. Interlayer migration causes irreversible transformation of the material. Intralayer migration makes it impossible for lithium ions to return to the same chemical environment as when they are deintercalated when they are re-embedded inside again, ultimately resulting in voltage hysteresis.
[0007] (3) Transition metal ion dissolution
[0008] Transition metal ions first dissolve from the surface of the material, then migrate through the electrolyte, and finally deposit on the negative electrode. The dissolution process of transition metal ions will cause capacity and voltage decay. In addition, the reduction / deposition of transition metals on the negative electrode increases the thickness of the solid electrolyte interface (SEI) layer, increases the battery impedance, and thus hinders the transmission of lithium ions.
[0009] (4) Surface side reactions
[0010] The surface of the material is unstable, and side reactions occur when it comes into direct contact with the electrolyte at the surface interface. A thick cathode electrolyte interface (CEI) layer is formed. Too thick CEI will prevent the diffusion of lithium ions, thereby reducing the electrochemical performance.
[0011] At present, in order to solve the above problems, manganese-based positive electrode materials are generally modified, and common treatment methods include doping and coating. However, doping and coating treatments are not only complicated in processing, but also have obvious limitations and cannot solve the problems existing in the application of manganese-based positive electrode materials. Therefore, it is necessary to develop a more effective treatment method. Summary of the invention
[0012] In view of the above-mentioned deficiencies in the prior art, the present invention provides a method for improving the cycle performance of manganese-based positive electrode materials, the prepared manganese-based positive electrode materials and applications. The present invention proposes a method for preparing manganese-based positive electrode materials by magnetic field and / or high-temperature plasma assisted calcination. This method neither introduces other elements nor modifies the surface of the manganese-based positive electrode material, thereby achieving the goal of not sacrificing the ultra-high specific capacity of the material itself, and improving its electrochemical performance by regulating the structure of the material itself.
[0013] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0014] A method for improving the cycle performance of a manganese-based positive electrode material, by reducing the spin state of manganese ions in the manganese-based material and then using the material to prepare the positive electrode material.
[0015] Furthermore, the spin state of manganese ions in the manganese-based material is reduced.
[0016] Furthermore, at least two of calcination, magnetic field assistance and high temperature plasma treatment are used to reduce the spin state of manganese ions in the manganese-based material.
[0017] Furthermore, the spin state of manganese ions in the manganese-based material is reduced by calcining in a magnetic field and / or a high-temperature plasma environment.
[0018] Furthermore, the calcination includes the whole process of heating, keeping warm and cooling down, and the magnetic field and / or high temperature plasma treatment can be carried out during the whole calcination process.
[0019] Furthermore, the specific process of reducing the spin state of manganese ions in the manganese-based material is as follows:
[0020] The dried manganese-containing precursor material is mixed with a lithium source, and then calcined at 300-500° C. for 5-10 hours in a magnetic field and / or a high-temperature plasma environment, and then heated to 800-1000° C. for 10-15 hours.
[0021] Furthermore, when magnetic field-assisted treatment is used to reduce the spin state of manganese ions in the manganese-based material, the magnetic field strengths during the two calcination processes are 0.2 to 0.5 T, respectively.
[0022] Furthermore, the magnetic field intensities of the two calcinations are 0.25-0.40 T respectively.
[0023] Furthermore, the first calcination temperature is 500° C. and the time is 5 h, and the second calcination temperature is 800° C. and the time is 12 h.
[0024] Further, the process of reducing the spin state of manganese ions in the manganese-based material is as follows:
[0025] The manganese-containing precursor material is mixed with a lithium source, and then placed in a plasma environment with a magnetic field strength of 0.2 to 0.5 T for treatment, so as to reduce the spin state of manganese ions in the manganese-based material.
[0026] Furthermore, the ratio of the molar number of lithium in the lithium-containing source material to the molar number of manganese in the manganese-containing precursor material is 0.5:1 to 5:1.
[0027] Furthermore, the ratio of the molar number of lithium element in the lithium-containing source material to the molar number of manganese element in the manganese-containing precursor material is 1.7:1 to 3:1.
[0028] Furthermore, the manganese-containing precursor material is a carbonate precursor or a hydroxide precursor.
[0029] Furthermore, the preparation method of the carbonate precursor is: mix manganese sulfate monohydrate with one or two of cobalt sulfate heptahydrate and nickel sulfate hexahydrate, dissolve them in deionized water at a ratio of the molar number of manganese element to the sum of the molar numbers of the two transition metals nickel and cobalt of 0.5:1 to 9:1, and then co-precipitate with Na2CO3 as a precipitant and ammonia water as a complexing agent to obtain a carbonate precursor.
[0030] Furthermore, when preparing the precursor, manganese sulfate monohydrate is mixed with one or two of cobalt sulfate heptahydrate and nickel sulfate hexahydrate, and the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and / or cobalt is 1:1 to 7:1.
[0031] Furthermore, when preparing the hydroxide precursor, NaOH solution is used as a precipitant; NH3·H2O solution is used as a complexing agent.
[0032] Furthermore, the lithium source is LiOH·H2O or Li2CO3.
[0033] The manganese-based positive electrode material prepared by the above method.
[0034] The above-mentioned manganese-based positive electrode material is used as a positive electrode in the preparation of lithium-ion batteries, metal lithium batteries, solid-state lithium batteries and negative electrode-free lithium batteries.
[0035] Beneficial effects of the present invention:
[0036] The present invention can change the original spin state of manganese ions in the manganese-based positive electrode material by applying a certain intensity magnetic field and / or high-temperature plasma treatment during calcination, so that its electrons undergo spin changes, thereby preparing a manganese-based positive electrode material with low-spin manganese ions. Compared with conventional methods such as ligand regulation and metal doping for regulating the spin state of manganese ions, the method of the present invention is more efficient, more stable, and has a simple process and no pollution, and can be applied on a large scale.
[0037] The present invention reduces the spin state of manganese ions by applying an external magnetic field and / or high-temperature plasma treatment. In the manganese-based positive electrode material with a low spin state, the lattice distortion caused by the Jan-Taylor effect can be significantly reduced, so that the material maintains a well-symmetrical regular octahedral field, thereby improving the cyclic stability of the material. At the same time, due to the magnetostrictive effect, the lattice constant is reduced, which is beneficial to the enhancement of the force of the TM-O bond and prolonging the service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The spin state characterization curves of the manganese-based positive electrode material prepared in Comparative Example 5 and the low-spin manganese-based positive electrode material prepared in Example 3;
[0039] Figure 2 1C discharge capacity curves of the manganese-based positive electrode material prepared in Comparative Example 5 and the low-spin manganese-based positive electrode material prepared in Example 3;
[0040] Figure 3 1C discharge capacity curves of the manganese-based positive electrode material prepared in Comparative Example 5 and the low-spin manganese-based positive electrode material prepared in Example 12;
[0041] Figure 4 1C discharge capacity curves of the manganese-based positive electrode material prepared in Comparative Example 5 and the low-spin manganese-based positive electrode material prepared in Example 15. DETAILED DESCRIPTION
[0042] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0043] Example 1
[0044] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0045] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 1:1;
[0046] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 3:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.25T and calcined at 300°C for 10 hours. The magnetic field strength is maintained at 0.2T, and then the temperature is raised to 1000°C and calcined for 10 hours to obtain the final product.
[0047] Example 2
[0048] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0049] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 2:1;
[0050] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2.26:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.25T and calcined at 400°C for 9 hours, the magnetic field strength is maintained at 0.25T, and then the temperature is raised to 900°C and calcined for 11 hours to obtain the final product.
[0051] Example 3
[0052] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0053] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 3:1;
[0054] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.30T and calcined at 500°C for 8 hours, the magnetic field strength is maintained at 0.30T, and then the temperature is raised to 800°C and calcined for 12 hours to obtain the final product.
[0055] Example 4
[0056] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0057] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 4:1;
[0058] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.88:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.35T and calcined at 500°C for 7 hours. The magnetic field strength is maintained at 0.35T, and then the temperature is raised to 800°C and calcined for 12 hours to obtain the final product.
[0059] Example 5
[0060] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0061] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for coprecipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 5:1;
[0062] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.8:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.40T and calcined at 500°C for 6 hours, the magnetic field strength is adjusted to 0.30T, and then the temperature is raised to 800°C and calcined for 11 hours to obtain the final product.
[0063] Example 6
[0064] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0065] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 6:1;
[0066] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.75:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.40T and calcined at 500°C for 5 hours, the magnetic field strength is adjusted to 0.50T, and then the temperature is raised to 800°C and calcined for 10 hours to obtain the final product.
[0067] Example 7
[0068] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0069] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 7:1;
[0070] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.70:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.40T and calcined at 500°C for 5 hours, the magnetic field strength is adjusted to 0.40T, and then the temperature is raised to 800°C and calcined for 10 hours to obtain the final product.
[0071] Example 8
[0072] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0073] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 5:1;
[0074] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.80:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.5T and calcined at 500°C for 5 hours, the magnetic field strength is adjusted to 0.5T, and then the temperature is raised to 800°C and calcined for 13 hours to obtain the final product.
[0075] Example 9
[0076] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0077] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 6:1;
[0078] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.75:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.35T and calcined at 500°C for 5 hours, the magnetic field strength is adjusted to 0.35T, and then the temperature is raised to 800°C and calcined for 14 hours to obtain the final product.
[0079] Example 10
[0080] A low-spin manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0081] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for coprecipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 7:1;
[0082] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.70:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a high-temperature annealing furnace with a magnetic field strength of 0.45T and calcined at 500°C for 5 hours, the magnetic field strength is adjusted to 0.45T, and then the temperature is raised to 800°C and calcined for 15 hours to obtain the final product.
[0083] Embodiment 11
[0084] A low-spin manganese-based positive electrode material prepared by plasma calcination, the preparation method of which is as follows:
[0085] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 3:1;
[0086] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 5:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. It is then placed in a plasma environment and oxygen is introduced, calcined at 500°C for 10 minutes, and then heated to 800°C for 10 minutes to obtain the final product.
[0087] Example 12
[0088] A low-spin manganese-based positive electrode material prepared by plasma calcination, the preparation method of which is as follows:
[0089] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 4:1;
[0090] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.88:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. Then, it is placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 10 minutes and then heated to 800°C for 10 minutes to obtain the final product.
[0091] Embodiment 13
[0092] A low-spin manganese-based positive electrode material prepared by plasma calcination, the preparation method of which is as follows:
[0093] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0094] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 3:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. It is then placed in a plasma environment and oxygen is introduced, calcined at 500°C for 20 minutes, and then heated to 800°C for 20 minutes to obtain the final product.
[0095] Embodiment 14
[0096] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0097] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 2:1;
[0098] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 2.26:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 20 minutes and then heated to 800°C for 20 minutes. A magnetic field of 0.20 T strength is applied to obtain the final product.
[0099] Embodiment 15
[0100] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0101] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0102] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, the amount of the two is based on the manganese element in the precursor material and the lithium element in Li2CO3, and the molar ratio of lithium to manganese is 3:1. Then it is placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 20 minutes and then heated to 800°C for 20 minutes. At the same time, a 0.30T magnetic field is applied to obtain the final product.
[0103] Example 16
[0104] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0105] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 2:1;
[0106] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2.26:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 20 minutes and then heated to 800°C for 10 minutes. At the same time, a 0.40T magnetic field is applied to obtain the final product.
[0107] Embodiment 17
[0108] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0109] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 7:1;
[0110] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.7:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 10 minutes and then heated to 800°C for 20 minutes. At the same time, a 0.50T magnetic field is applied to obtain the final product.
[0111] Embodiment 18
[0112] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0113] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 6:1;
[0114] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 1.75:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 10 minutes and then heated to 900°C for 10 minutes. A magnetic field of 0.50 T strength is applied to obtain the final product.
[0115] Embodiment 19
[0116] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0117] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using NaOH as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a hydroxide precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 9:1;
[0118] (2) After the hydroxide precursor is dried at 120°C for 12 hours, it is mixed with LiOH·H2O, and the molar ratio of lithium to manganese is 0.5:1 based on the manganese element in the precursor material and the lithium element in LiOH·H2O. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 300°C for 10 minutes and then heated to 800°C for 10 minutes. A magnetic field of 0.50 T strength is applied to obtain the final product.
[0119] Embodiment 20
[0120] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0121] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 5:1;
[0122] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.80:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 10 minutes and then heated to 1000°C for 20 minutes. At the same time, a 0.40T magnetic field is applied to obtain the final product.
[0123] Embodiment 21
[0124] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0125] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 6:1;
[0126] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.80:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 300°C for 10 minutes and then heated to 900°C for 20 minutes. At the same time, a 0.40T magnetic field is applied to obtain the final product.
[0127] Embodiment 22
[0128] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0129] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 7:1;
[0130] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.70:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 400°C for 10 minutes and then heated to 1000°C for 20 minutes. At the same time, a 0.30T magnetic field is applied to obtain the final product.
[0131] Embodiment 23
[0132] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0133] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 5:1;
[0134] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 1.80:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 10 minutes and then heated to 800°C for 20 minutes. A magnetic field of 0.3 T strength is applied to obtain the final product.
[0135] Embodiment 24
[0136] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0137] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0138] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, the amount of the two is based on the manganese element in the precursor material and the lithium element in Li2CO3, and the molar ratio of lithium to manganese is 3:1. Then it is placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 20 minutes and then heated to 800°C for 10 minutes. At the same time, a 0.40T magnetic field is applied to obtain the final product.
[0139] Embodiment 25
[0140] A low-spin manganese-based positive electrode material prepared by plasma and magnetic field assisted calcination, the preparation method of which is as follows:
[0141] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 2:1;
[0142] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2.26:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced, calcined at 800°C for 20 minutes, and a 0.40T magnetic field is applied to obtain the final product.
[0143] Embodiment 26
[0144] A low-spin manganese-based cathode material prepared with the assistance of high-temperature plasma and magnetic field, the specific process is as follows:
[0145] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 3:1;
[0146] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced, treated at 800°C for 10 minutes, and a magnetic field of 0.40T is applied to obtain the final product.
[0147] Comparative Example 1
[0148] A manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0149] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 1:1;
[0150] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 3:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.10T and calcined at 500°C for 7 hours, the magnetic field strength is maintained at 0.10T, and then the temperature is raised to 800°C and calcined for 12 hours to obtain the final product.
[0151] Comparative Example 2
[0152] A manganese-based positive electrode material prepared by magnetic field-assisted calcination, the preparation method of which is as follows:
[0153] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor is 1:1;
[0154] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 3:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace with a magnetic field strength of 0.20T and calcined at 200°C for 7 hours, the magnetic field strength is maintained at 0.20T, and then the temperature is raised to 1200°C and calcined for 12 hours to obtain the final product.
[0155] Comparative Example 3
[0156] A manganese-based positive electrode material prepared by high-temperature plasma and magnetic field assistance, the preparation method of which is as follows:
[0157] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0158] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, the amount of the two is based on the manganese element in the precursor material and the lithium element in Li2CO3, and the molar ratio of lithium to manganese is 3:1. It is placed in a plasma environment and oxygen is introduced. It is calcined at 500°C for 20 minutes and then heated to 800°C for 10 minutes. At the same time, a 0.10T magnetic field is applied to obtain the final product.
[0159] Comparative Example 4
[0160] A manganese-based positive electrode material prepared by high-temperature plasma and magnetic field assistance, the preparation method of which is as follows:
[0161] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0162] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 3:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a plasma environment and oxygen is introduced. It is calcined at 200°C for 20 minutes and then heated to 500°C for 10 minutes. At the same time, a 0.30T magnetic field is applied to obtain the final product.
[0163] Comparative Example 5
[0164] A manganese-based positive electrode material, the preparation method of which is as follows:
[0165] (1) dissolving manganese sulfate monohydrate, cobalt sulfate heptahydrate, and nickel sulfate hexahydrate in deionized water, using Na2CO3 as a precipitant and ammonia water as a complexing agent for co-precipitation to obtain a carbonate precursor, wherein the ratio of the molar number of manganese to the sum of the molar numbers of the two transition metals nickel and cobalt in the obtained precursor material is 1:1;
[0166] (2) After the carbonate precursor is dried at 120°C for 12 hours, it is mixed with Li2CO3, and the molar ratio of lithium to manganese is 2:1 based on the manganese element in the precursor material and the lithium element in Li2CO3. It is then placed in a high-temperature annealing furnace and calcined at 500°C for 6 hours, and then heated to 800°C and calcined for 12 hours to obtain the final product.
[0167] The electrochemical properties of the manganese-based positive electrode materials prepared in Examples 1 to 26 of the present invention and Comparative Examples 1 to 5 were tested, and the results are shown in Table 1. Then, the 1C discharge capacity of the low-spin state manganese-based positive electrode materials prepared in Examples 3, 12 and 15 of the present invention and Comparative Example 5 was tested, and the spin state of the manganese-based positive electrode materials prepared in Example 3 and Comparative Example 5 was characterized, and the results are shown in Table 1. Figures 1 to 4 .
[0168] Table 1 Electrochemical performance
[0169]
[0170]
[0171]
[0172] As shown in Table 1 and Figures 2 to 4 As shown, compared with comparative examples 1 to 5, the electrochemical performance of the manganese-based positive electrode material with a low spin state prepared by the technical scheme described in Examples 1 to 26 of the present invention is more excellent, indicating that only by the technical scheme of the present invention can a manganese-based positive electrode material with excellent electrochemical energy in a low spin state be prepared.
[0173] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for improving the cycle performance of a manganese-based positive electrode material, characterized in that: The spin state of manganese ions in manganese-based materials is reduced, and then positive electrode materials are prepared therefrom.
2. The method according to claim 1, characterized in that At least two of calcination, magnetic field assistance and high-temperature plasma treatment are used to reduce the spin state of manganese ions in the manganese-based material.
3. The method according to claim 2, characterized in that The spin state of manganese ions in the manganese-based material is reduced by calcination combined with magnetic field assistance and / or high temperature plasma treatment.
4. The method according to claim 3, characterized in that The process of reducing the spin state of manganese ions in manganese-based materials is as follows: The dried manganese-containing precursor material is mixed with a lithium source, and then calcined at 300-500° C. for 5-10 hours in a magnetic field and / or a high-temperature plasma environment, and then heated to 800-1000° C. for 10-15 hours.
5. The method according to claim 4, characterized in that When the magnetic field-assisted treatment is used to reduce the spin state of manganese ions in the manganese-based material, the magnetic field intensity during the two calcination processes is 0.2-0.5T respectively.
6. The method according to claim 2, characterized in that The process of reducing the spin state of manganese ions in manganese-based materials is as follows: The manganese-containing precursor material is mixed with a lithium source and then placed in a high-temperature plasma environment with a magnetic field strength of 0.2 to 0.5 T to reduce the spin state of manganese ions in the manganese-based positive electrode material.
7. The method according to claim 4 or 6, characterized in that: The ratio of the molar number of lithium element in the lithium-containing source material to the molar number of manganese element in the manganese-containing precursor material is 0.5:1 to 5:
1.
8. The method according to claim 7, characterized in that The manganese-containing precursor material is a carbonate precursor or a hydroxide precursor; the lithium source is LiOH·H2O or Li2CO3.
9. A manganese-based positive electrode material prepared by the method according to any one of claims 1 to 8.
10. Use of the manganese-based positive electrode material according to claim 9 as a positive electrode in the preparation of lithium-ion batteries, metal lithium batteries, solid-state lithium batteries and negative electrode-free lithium batteries.
Citation Information
Patent Citations
Preparation method of spinel lithium manganate and application of spinel lithium manganate
CN104659355A
Electromagnetic field-constrained plasma enhanced oxidation calcination method of high-nickel positive electrode material of lithium ion battery
CN106992296A
Preparation method of manganese-based cathode material for lithium ion batteries
CN107845807A
Method for preparing flaky single crystal high-nickel nickel-cobalt-manganese ternary material at high pressure
CN112553690A
Magnetic field modified lithium ion battery ternary material and preparation method thereof
CN115490277A